The Expression and Significance of Feces Cyclooxygensae-2 mRNA in Colorectal Cancer and Colorectal Adenomas - Li, Xiaofeng (Saudi J Gastroenterol, 2017)
BACKGROUND/AIM: This study aims to explore the expression and significance of feces cyclooxygensae-2 (COX-2) mRNA in colorectal cancer and colorectal adenomas. MATERIALS AND METHODS: The expression of feces COX-2 mRNA in colorectal cancer (n = 28), colorectal adenomas (n = 54), and normal control group (n = 11) were examined by reverse transcriptase polymerase chain reaction (RT-PCR). The positive rate of fecal occult blood test (FOBT) were detected in colorectal cancer (n = 30), colorectal adenomas (n = 56), and normal control group (n = 11); the sensitivity of the two methods was also compared. RESULTS: The positive rate of feces COX-2 mRNA in colorectal cancer was 82.1% (25/28), which was significantly higher than colorectal adenomas 59.3% (32/54), and normal tissues 18.2% (2/11), the difference being significant between the three groups (χ(2)= 13.842, P = 0.001). The positive rate of FOBT in colorectal cancer was 73.3% (10/30), which was significantly higher than colorectal adenomas 10.7% (6/56) and normal tissues 9.1% (1/11), the difference being significant between these three groups (χ(2)= 7.525, P = 0.023). There was no significant association between feces COX-2 expression and various clinical pathological features of colorectal cancer and colorectal adenomas (P > 0.05). The sensitivity of the RT-PCR method is higher than FOBT, however, the specificity of FOBT is slightly higher than RT-PCR. CONCLUSIONS: High expression of feces COX-2 mRNA in colorectal adenomas and colorectal cancer is a common event; it is an early event in the development of colorectal adenomas to colorectal cancer. Feces COX-2 mRNA has a high sensitivity for detect colorectal cancer; combination with FOBT will be the best alternative. Feces COX-2 can be potentially used in the early diagnosis and screening of colorectal cancer.